STIGMASTERYL ESTER FROM ARTEMISISA ANNUA} L. HAIRY ROOT CUTURES EXTRACT AND CANARIUM VULGARE} L. OIL AND ITS ANTI HYPERCHOLASTEROLEMIA ACTIVITY TES - Aju Tofiana, Fadjar
In 2012, heart disease and stroke is number one prominent cause ofdeath in the world. Unhealthy diets and lack of physical activity are critical factors causing heart disease and stroke. Several ways of treating these diseases are consuming healthy diets such as fruits and vegetables, which contains phytosterol. Phytosterol is a functional component proven scientifically able to lower cholesterol level. Consuming 2 g / day of plant stanols in ester form lower cholesterol level by 10%. The aim of this study was to obtain stigmasteryl ester by means of transesterification of Canarium vulgare L. oil with Artemisia annua L. hairy root cultures extract rich in stigmasterol carried out in dry dichloromethane applying CaO as catalyst and data on its in vivo anti hypercholesterolemia activity. annua hairy root cultures as source ofphytosterol were used to utilize the byproducts of artemisinin production. Before transesterification synthesis was performed, a pre emptive esterification synthesis between siigmasierol was done using oleic acid, palmitate acid, stearic acid to produce esterification product (EP), which are stigmasteryl oleate, stigmasteryl palmitate, and stigmasteryl stearate respectively. EP is used as reference compounds of qualitative and quantitative of transesterification product (TP). Anti hypercholesterolemia TP activity test was performed in vivo to female Wistar rat. Ezetimibe and product which contains commercial plant sianol ester were used as standard. The result of the plant species determination confirmed that the canarium plant used was Canarium vulgare L. Characterisation of the vulgare oil showed that it had a water content of 0.25%, density of 0.8845 g/cm3, acid value of 0.04; saponification value of 0.62; and esterification value of 34.79. The oil contained such as 40.7% oleic acid; 40.4% palmitic acid, and 16.4% stearic acid. Infrared (IR) spectrum showed absorption bands at 1747.19 cm-I (C=O stretch) and 1569.77 cm-I (C=C stretch)for oleic acid. The optimum harvesting time was reached in the 5th week Wilh a stigmasterol concentration of 1.5%. The thin layer chromatography profile of 8 annua hairy root cultures extract showed a spot with Rf of 0.1 which was in line with that of stigmasterol standard. GC-MS analysis showed that the extract consisted of phytosterol compounds with composition relatively are 74.6% of stigmasterol, 13.5% of ß-sitosterol, 11.9% of campesterol with retention time (RT) of 25.4; 25.9; 25.2 min and molecular weight (MW) of 412.5; 414.5; 400.7 respectively. In addition, stigmasteryl oleate with a RT 23.7 min and MW of 676.8, was identified IR spectrum showed absorption bands ai 3347.82 cm-I (-0H stretch); at 1658.48 cm-I (C—C stretch) and at 1103.08 cm 1 (C-O stretch) for stigmasterol. The EP of oleic acid, palmitate acid and stearic acid with stigmasierol were white solids with melting points of respectively 40.8 — 42.0, 41.0 42.0, 56.3 — 56.6 oc as well as Rf values of 0.8, 0.9, 0.86 applying ethyl acetate:n-hexane—l:9 as developing solvent. The yields of stigmasteryl oleat, stigmasteryl palmitate, stigmasteryl stearate were 4.2, 21.5, 11.8%, respectively. The IR spectra of the 3 EP showed absorbance bands of stretch at 1727.91 cm-I , and stretch at 1072,23 cm 1 - 1083,8 cm- were observed, confirming the presence of ester compound. In case of stigmasteryl oleate, an absorbance band of C=C stretch at 1650.77 cm-I was also observed. In IH-NMR spectrometry of 3 EP, chemical shifts of proton attached to carbon atom bound to OH group of stigmasterol, shiftedfrom 3.52 ppm (stigmasterol) to 4.61 ppm (ester). In the GCMS analysis ofEP, peaks with RTof23.8, 16.9, 15.0 min and m/z values of 676,8; 650, 6; 679.8 were observed, confirming the MW of stigmasteryl oleate, stigmasteryl palmitate and stigmasteryl stearale respectively. The TP of vulgare oil with annua hairy root cultures extract, was yellow brownish semi-solid. The IR spectrum of TP showed absorbance bands of C=O stretch at 1743.33 cm-I, stretch at 1160.94 cm-I and C=C stretch at 1461, 78 cm- were observed, confirming the presence of stigmasteryl oleate. In the GC-MS analysis of TP, peaks with RT of 23.8; 16.8; 15.0 min and m/z values of 676. l; 650.0; 679.6 were observed, confirming the MW of stigmasteryl oleate, stigmasteryl palmitate and stigmasteryl stearate respectively. The concentration ofstigmasteryl oleate in TP was 1.67%. Antihypercholesterolemia activity test results show that on the 12th day, cholesterol level of TP group decrease by (30.3%), while that of control group was (20.2%). The difference is significant statistically (p < 0.05). Meanwhile the cholesterol level ofezetimibe group decreased by (45.7%) and that of x product group by (21.0%). It can be concluded that transesterification product between vulgare oil and stigmasterol-rich extract of 4. annua hairy root cultures shows the cholesterollowering effect to animal model.